2022
DOI: 10.3390/v14020198
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune Responses, Immune Escape and Immune-Mediated Pathogenesis during HDV Infection

Abstract: The hepatitis delta virus (HDV) is the smallest known human virus, yet it causes great harm to patients co-infected with hepatitis B virus (HBV). As a satellite virus of HBV, HDV requires the surface antigen of HBV (HBsAg) for sufficient viral packaging and spread. The special circumstance of co-infection, albeit only one partner depends on the other, raises many virological, immunological, and pathophysiological questions. In the last years, breakthroughs were made in understanding the adaptive immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 188 publications
(261 reference statements)
0
9
0
Order By: Relevance
“…This can hamper HDV clearance and in turn contributing to the persistence of HDV‐infection 34 . In particular, a previous study has revealed the presence of immune‐escape mutations in 6 out of the 11 (54%) analysed CD8+ T‐cell epitopes 34 . Notably, another study has identified the mutation S170N, located in an HLA‐B*15:01‐restricted CD8+ T‐cell epitope, conferring an immune‐evasion phenotype in all patients with this specific HLA 34 …”
Section: Mechanisms Underlying Hdv Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…This can hamper HDV clearance and in turn contributing to the persistence of HDV‐infection 34 . In particular, a previous study has revealed the presence of immune‐escape mutations in 6 out of the 11 (54%) analysed CD8+ T‐cell epitopes 34 . Notably, another study has identified the mutation S170N, located in an HLA‐B*15:01‐restricted CD8+ T‐cell epitope, conferring an immune‐evasion phenotype in all patients with this specific HLA 34 …”
Section: Mechanisms Underlying Hdv Persistencementioning
confidence: 99%
“…(Figure 1). This can hamper HDV clearance and in turn contributing to the persistence of HDV‐infection 34 . In particular, a previous study has revealed the presence of immune‐escape mutations in 6 out of the 11 (54%) analysed CD8+ T‐cell epitopes 34 .…”
Section: Mechanisms Underlying Hdv Persistencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a portion of HBV patients are co-infected with hepatitis D virus (HDV), which often indicates a poor prognosis. As the smallest known human virus, HDV has perfectly adapted to escape recognition by CD8 + T cells restricted by common human leukocyte antigen (HLA) class I alleles ( 120 ). A recent study suggested that antigen-nonspecific activation of hepatic CD8 + T RM cells may be involved in intrahepatic inflammation and disease progression in HDV infection ( 121 ).…”
Section: Liver T Rm Cells In the Chronic Liver Dis...mentioning
confidence: 99%
“…Notably, the mechanisms driving the sequence variation of HDV have so far not been studied in detail. In recent studies, it has been shown also for HDV that CD8 + T cells contribute to sequence variation by selecting mutations in targeted epitopes ( 15 , 16 ). HLA class I-associated selection pressure on HDV was also documented at the population level ( 17 ).…”
Section: Introductionmentioning
confidence: 99%